2005
DOI: 10.1007/s11060-004-6152-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Drug Resistance Proteins Pgp, MRP1, MRP3, MRP5 AND GST-π in Human Glioma

Abstract: Chemotherapy in glioma is poorly effective: the blood-brain barrier and intrinsic and/or acquired drug resistance of tumor cells could partly explain this lack of major effect. We investigated expression of P-glycoprotein (Pgp), multidrug resistance protein (MRP) 1, MRP3, MRP5 and glutathione-S-transferase pi (GST-pi) in malignant glioma patients. Cytofluorimetric analysis of 48 glioma specimens and 21 primary cultures showed high levels of MRP1, moderate levels of MRP5 and low levels of Pgp, GST-pi and MRP3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
137
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 33 publications
7
137
2
5
Order By: Relevance
“…Accordingly, our results showed that the ATP-dependent efflux transporter Mrp1 was highly expressed in NS, following by a decrease along differentiation. Regarding GL261 cells, the levels of Mrp1 expression were also very high, such as previously detected in glioma samples and in glioma cell lines [61,62] . Since Mrp1 expression is significantly up-regulated in cancer stem-like cells (CD133+ cells), isolated from GBM [63] , and given that these undifferentiated tumor cells share some properties with 86 www.ommegaonline.org…”
Section: Discussionsupporting
confidence: 64%
“…Accordingly, our results showed that the ATP-dependent efflux transporter Mrp1 was highly expressed in NS, following by a decrease along differentiation. Regarding GL261 cells, the levels of Mrp1 expression were also very high, such as previously detected in glioma samples and in glioma cell lines [61,62] . Since Mrp1 expression is significantly up-regulated in cancer stem-like cells (CD133+ cells), isolated from GBM [63] , and given that these undifferentiated tumor cells share some properties with 86 www.ommegaonline.org…”
Section: Discussionsupporting
confidence: 64%
“…MRP1 is an important multidrug transporter in the brain [11,12] , despite the fact that it is mainly distributed in the choroid plexus and ependymal epithelial cells and is found in lower levels in neurons and glial cells in the normal brain [13,14] . This trend is consistent with our observation that MRP1 mRNA and protein levels were low in the cortex and hippocampus of normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…MRP1 and MRP5 are expressed in normal human astrocytes and endothelial cells. High levels of MRP1, moderate levels of MRP5, and low levels of MRP3 were found in tumor cells of malignant glioma patients, suggesting that MRP1 may be responsible for tumor cells' resistance to chemotherapy in the brain [11] . MRP1 can cause resistance to arsenite, while MRP2 can result in resistance to cisplatin [9] .…”
Section: Discussionmentioning
confidence: 99%
“…asimismo, la actividad de este transportador fue confirmada en estas células cancerosas y es susceptible de ser inhibido utilizando un bloqueador específico. Otros estudios utilizando análisis citofluorimétrico de diferentes especíme-nes de gliomas y sus cultivos primarios, también indican que existe un alto nivel de expresión de la proteína Mrp1, moderados niveles de Mrp5 y bajos niveles de Mrp3, Mrp2 y P-gp 12,13 . además, estudios en líneas celulares de gliomas corroboran un predominante contenido de miembros de la subfamilia MRP, particularmente Mrp1 14 .…”
Section: Discussionunclassified
“…Existen estudios, usando diferentes especímenes de gliomas y sus cultivos primarios, que demuestran un predominante contenido de miembros de la subfamilia MRP, particularmente Mrp1 pero bajos niveles de P-gp y otros transportadores abc en gliomas de alto grado [12][13][14] .…”
unclassified